Peran Komunikasi Interpersonal dalam Meningkatkan Kinerja Tim Kerja - Hilda Rahmadhani Nasution; Silvia Vinka Syahfitri (MES Management Journal, 2024)
The purpose of this article is to discuss interpersonal communication in improving performance, work teams. As it is known that the existence of human resources plays a very important role in an agency. Employees as motivated human resources will carry out an activity or task as well as possible so as to provide maximum work results. In an organization or agency, communication activities are one of the most important activities. The type of research used by the author is library research, namely research that only uses library collection materials without any field research. the author obtains data based on the library in the form of books, journals, documents and so on. This research can only be answered through library research and it is impossible to expect from field research data. The results showed that interpersonal communication carried out by the Work Team aims to create a good relationship between one employee and another. This relationship has an impact on the emergence of an attitude of openness and trust obtained from interpersonal relationships in the work environment. In the work environment, an employee's performance will be good when the employee has a good interpersonal communication pattern and vice versa. Interpersonal communication carried out by the work team becomes a practical communication pattern that is useful in establishing relationships with work partners, leaders and fellow employees, as well as managerial levels that require interpersonal communication.